Prenatal Diagnosis of Fetal Peters’ Plus Syndrome: A Case Report - Neerja Gupta; Anita Kaul; Madhulika Kabra (Case Reports in Genetics)
Peters’ plus syndrome is a rare but clinically recognizable autosomal recessive ocular genetic syndrome. Diagnosis during the fetal life is challenging due to the presence of nonspecific findings such as ventriculomegaly in the growth-retarded fetuses. We report the first case of fetal Peters’ plus syndrome from India, where fetal ultrasound and the family history were helpful in providing a clue to the diagnosis that was confirmed later on by the DNA analysis.